Language and power in brazilian and portuguese media - Seara, Isabel Roboredo (2020)
This study proposes to broaden the theoretical discussion about referencing by analyzing opinion articles dealing with themes associated with violence, published in the media in Portugal and Brazil. In the theoretical perspective, topics related to the co-referentiality and inferentiality necessary for the identification of speech objects will be discussed, following the theoretical support of Text Linguistics and other researches with textual-discursive bias, such as Fonseca (1992), Fuchs (1992), Apotheloz and Reichler-Béguelin (1995), Koch and Marcuschi (1998), Mondada and Dubois (2003), Cornish (2011) Maalej (2011), Pecorari (2015), Cabral and Santos (2016), among others. We also invoke some assumptions about argumentation, basing the reflection on the studies of Ducrot (1988), Charaudeau (2008) and Amossy (2008, 2009). Our purpose is to describe the behavior of anaphora as axiological markers of the argumentative conduction of politically themed texts, polarizing the complex power network. Therefore, we intend to collaborate in the interface studies between referencing and textual genre, specifically in the case of textual genres to which readers have easy access via the web, demonstrating how anaphora and deixis can help to ideologically mark the text.